Studi literatur: Tantangan dan kendala dalam implementasi pembelajaran STEAM - Badriyah, Lailatul (Maliki Interdisciplinary Journal, 2024)
In this 21st century, students are required to develop century skills that include critical thinking skills and problem solving, cooperation, communication, and developing creativity. To meet these demands, teachers need to choose the right and appropriate teaching methods, one of which is STEAM-based learning. This STEAM-based learning combines several subjects in one learning. In the implementation of STEAM-based learning, it can include 21st century skills so that STEAM can be an appropriate alternative that teachers can use in learning. However, in the implementation of learning activities, of course, it does not run smoothly. This article specifically discusses the challenges and obstacles that exist in implementing this STEAM-based learning. The research method used in this article is a literature study of several journal articles related to challenges in STEAM-based learning. The results of the study revealed that there are several challenges in STEAM-based learning, namely teacher unpreparedness and lack of socialization, inadequate supporting facilities, lack of parental support, limited student handbooks, and insufficient budget and time.